Marshall Islands : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in the Marshall Islands during 1996-98. Real GDP declined by 15.2 percent and 5.3 percent in FY1996 and FY1997, respectively, reflecting mainly the effects of the adjustment measures implemented by the government since 1996 under the Policy Reform Program aimed at correcting the large imbalances in the public finance and external sector. Agriculture and fishing activities declined in FY1996 but recovered partially the following year. Construction fell sharply in FY1996 and stagnated in FY1997 with no new major projects following the completion of a 150-room hotel and the dry dock.